A new dammarane type triterpene glucoside from the aerial parts of Gouania longipetala (Rhamnaceae). Issue 19 (2nd October 2021) - Désiré, Soh; Ernestine, Nkwengoua; Bruno, Tchebemou Bakang; Lazare, Sidjui Sidjui; Ulrich, Dzo Defokou; Lateef, Mehreen; Schneider, Bernd; Ali, Muhammad Shaiq; Barthélemy, Nyassé
Abstract: 3-O- β -D-glucopyranosyl gouanogenin A (1 ), a new naturally occurring dammarane class of triterpene glucoside, has been isolated from the aerial parts of Gouania longipetala along with six known secondary metabolites 2–7 . Their structure was elucidated through spectroscopic data including 1 D- and 2 D-NMR. The compounds 1 and 6 showed significant antioxidant potential in DPPH radical scavenging assay. On the other hand, the compound 4 revealed potent inhibitory potential against the enzyme urease, while 1 and 3 were significantly active. Abstract : UF0001